Strategy for Improving Taxpayer Compliance through the Giving of Tax Incentives PPh 21 Borne by the Government during the Covid-19 Pandemic at KPP Pratama Bekasi Utara - Vita Vitasia; Trie Andari Ratna; Dwikora Harjo; Erika Oktavia (Yayasan Ilomata, 2022)
This study was conducted to analyze the strategy of increasing taxpayer compliance through theprovision of Pph 21 Tax Incentives borne by the government during the covid-19 pandemic at KPPPratama North Bekasi in 2020. The results of this study indicate that the implementation has not beengoing well because there are still many tax payers who have not do neso.reporting on the use of incentives. In this study, the author uses Richard's theory of strategy which according to him in general,the core of the strategy there are three entities, namely Problem Identification, Guiding Policy and Coherent Action.The approach use din this research is qualitative with descriptive method.Data collection in this study is by observation, documentation and interviews. The results of this study indicatethat the implementation has not gone well because there are still many taxpayers who have not reportedthe use of incentives. There are obstacles faced by KPP Pratama Bekasi Utara, including the lack of awareness of tax payers that need tobe improved,and difficulties in reporting due to the lack of information related to reporting on the use of tax incentives. Then, when tax payers are going to reportonline, the DGT server often has problems or experiences errors when they want to report. As a result,there was a delay in submitting the report.This has resulted in the low realization of tax payer compliance.